Perception and practices of folk medicines among youth in Pakistan - Rani, Samina; Rehman, Adeela; Mohamad Diah, Nurazzura (Global Research & Development Services (GRDS), 2015)
This study is aimed at exploring the relationship between perception and practices of folk medicines among youth in Pakistan. The quantitative research method was adopted to achieve its objectives. Structured questionnaires were distributed among respondents to collect data. The respondents were youth whose ages range from 18 to 25 residing in twin cities Rawalpindi and Islamabad in Pakistan. The data was analyzed using Statistical analysis Package of Social Sciences (SPSS version 13). The result showed that Pakistan youth have limited knowledge about folk medicines, and they do not have positive perceptions about folk medicines. As the result shows, youth do not perceive folk medicines positively; therefore their practices of folk medicines are limited. Majority of them know the importance and usage of folk medicines but do not know how to prepare them and where to get them. Findings shows that lack of educational awareness about folk medicines have a strong impact on folk medicine practices. Pakistani youth mostly prefer specialized doctors for their treatment rather than applying home-based treatment due to rapid cure and they perceived folk treatment to be slow in curing illnesses. It is recommended that folk wisdom about the usage of traditional healing practices must be transferred to the next generation by their elders as well as via education based awareness campaigns.